2013
DOI: 10.1017/s1751731113000888
|View full text |Cite
|
Sign up to set email alerts
|

Reducing GHG emissions through genetic improvement for feed efficiency: effects on economically important traits and enteric methane production

Abstract: Genetic selection for residual feed intake (RFI) is an indirect approach for reducing enteric methane (CH4) emissions in beef and dairy cattle. RFI is moderately heritable (0.26 to 0.43), moderately repeatable across diets (0.33 to 0.67) and independent of body size and production, and when adjusted for off-test ultrasound backfat thickness (RFIfat) is also independent of body fatness in growing animals. It is highly dependent on accurate measurement of individual animal feed intake. Within-animal repeatabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
3
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(119 citation statements)
references
References 94 publications
(173 reference statements)
6
106
3
4
Order By: Relevance
“…Thus, genetic improvement of feed conversion efficiency reduces the total manure produced and consequently reduces the emissions of CH 4 and N 2 O while maintaining productivity . In dairy and beef cattle, genetic selection for residual feed intake has shown that this indirect approach to reducing CH 4 emission is moderately heritable (0.26 to 0.43) and moderately repeatable across diets (0.33 to 0.67), indicating that the inclusion of this trait in the TMI could effectively reduce CH 4 emissions (Basarab et al, 2013). In developing countries, where economic resources for selection are insufficient, CH 4 and N 2 O emission reduction from enteric and manure fermentation can be achieved with the financial support of international donors (Arakelyan & Moran, 2015;Samaniego & Schneider, 2015) and with the aggregation of countries that have similar selection interests.…”
Section: Selectionmentioning
confidence: 99%
“…Thus, genetic improvement of feed conversion efficiency reduces the total manure produced and consequently reduces the emissions of CH 4 and N 2 O while maintaining productivity . In dairy and beef cattle, genetic selection for residual feed intake has shown that this indirect approach to reducing CH 4 emission is moderately heritable (0.26 to 0.43) and moderately repeatable across diets (0.33 to 0.67), indicating that the inclusion of this trait in the TMI could effectively reduce CH 4 emissions (Basarab et al, 2013). In developing countries, where economic resources for selection are insufficient, CH 4 and N 2 O emission reduction from enteric and manure fermentation can be achieved with the financial support of international donors (Arakelyan & Moran, 2015;Samaniego & Schneider, 2015) and with the aggregation of countries that have similar selection interests.…”
Section: Selectionmentioning
confidence: 99%
“…Selection for lower RFI should reduce feed production requirements in confinement dairy systems or permit increased stocking density in grazing systems. Based on models developed by Little et al (2008), selection for reduced RFI over a 25-year period in beef cattle production could reduce the total farm area required to support animal production by 13% and reduce the carbon footprint by 14% (Basarab et al, 2013). Although similar models for the effects of reducing RFI in dairy cattle have not been evaluated, a model evaluating improvements in GFE measured as reduced feed intake for the same level of energy-corrected milk yield indicated that improving GFE by one phenotypic standard deviation should reduce land use required for feed production by 6.7% per cow (or 4.2% for one genetic standard deviation; Bell et al, 2012).…”
Section: Benefits Of Selection For Improved Efficiency As Rfimentioning
confidence: 99%
“…Generally, as feed intake increases, additional substrate is available for rumen fermentation and methane production (Basarab et al, 2013). Hence, selection for lower RFI should permit significant reductions in methane emissions by decreasing average DMI of the herd.…”
Section: Benefits Of Selection For Improved Efficiency As Rfimentioning
confidence: 99%
See 2 more Smart Citations